Power augmentation and Ramp-Up rate improvement through compressed air Injection: a dry low NOx combustor CFD analysis - Wiranegara, Raditya Yudha; Igie, Uyioghosa; Szymanski, Artur; Abudu, Kamal; Abbott, David; Sethi, Vishal (Elsevier, 2024)
Gas turbines play a key role in accelerating the transition towards more environmentally friendly power generation. This role includes backup of renewable generation that is intermittent, providing grid inertia as well as other ancillary services for grid stability. For quick backup power, the ramp-up rate of gas turbines can be improved through air injection at the back of the compressor, facilitated by integrating compressed air energy storage. Published works have mostly focused on low-fidelity engine system analysis of air injection overall effects. No study has focused on the detailed combustor performance presented in this study. The work shows the impact of air injection on the emissions, thermoacoustic stability and liner wall durability. These yardsticks in assessing the operability of the combustor have also been used for air power augmentation and ramp-up analysis. ANSYS software was used in the computational fluid dynamics (CFD) analysis of the three-dimensional dry low NOx combustor. Low-order models were used for the thermoacoustic stability and durability analysis. For the power augmentation study, the NO and CO emissions produced at 15 % air injection are below the maximum values of the combustor in design operations. Also, the stability and durability were within limits. The ramp-up investigation indicates up to 10 % air injection is allowed and the emissions are similarly acceptable. However, the thermoacoustic analysis shows a potential for combustion instabilities at high frequencies above 1800 Hz. Generally, there was no unusual wall liner durability in these two studies. When benchmarked against previous engine-level analysis, the ramp-up rate can be potentially improved by 54 % if the small concern on thermoacoustic instability is resolved.
Keywords: Air Injection; Ramp-up rate; Power augmentation; Combustion; Emissions; Stability